Affective mediators of the influence of climate social resilience on young fishermen's life satisfaction in Malaysia's coastal degions - Zaremohzzabieh, Zeinab; Mohamed Shaffril, Hayrol Azril; Abdullah, Haslinda (Green Wave Publishing of Canada, 2023)
This study delves into the effects of climate change on the coastal regions of Malaysia, with a specific focus on fishing communities and the vulnerability of young fishermen. Recognizing the potential impact on their mental well-being, the researchers aim to understand how climate change influences the life satisfaction of these individuals and investigate the role of positive and negative emotions in this context. The study engages 400 participants who completed questionnaires encompassing social climate resilience, positive and negative emotions, and overall life satisfaction. The results of the study uncover a noteworthy association between social climate resilience and life satisfaction among young fishermen. It becomes evident that those who exhibit higher levels of resilience in coping withclimate-related changes tend to experience greater life satisfaction. Moreover, an intriguing finding emerges as positive emotions play a crucial mediating role in this relationship. In fact, positive emotions fully account for the link between resilienceand life satisfaction, emphasizing their significant influence on the well-being of young fishermen. This study provides valuable insights into the well-being of young fishermen in the face of climate change and the crucial role of positive emotions in shaping their life satisfaction. The findings highlight the need to develop strategies and interventions that foster resilience and promotepositive emotional well-being among young fishermen, ultimately enhancing their life satisfaction.